PENGARUH PEMANFAATAN AIR KELAPA SEBAGAI BAHAN SUBSTITUSI CAMPURAN BETON PRACETAK METODE SELF COMPACTING CONCRETE (SCC) - Said, Sugira; Nurhidayah, Nurhidayah (Universitas Bina Taruna Gorontalo, 2024)
Concrete mixtures are usually made with drinking water or pure water. However, if we are in a difficult condition to get clean water, we must try to use additional materials or waste around us. This is also a difficulty in the construction industry; one of the challenges is how to develop new ideas, such as high-quality and durable concrete (sustainability), from existing materials, such as coconut water. The data collection strategy for this study is laboratory-based. Given that the variables studied in this study include the composition of coconut water used to determine the quality of the concrete mixture, its compressive strength, and its comparison with ordinary water. The compressive strength of self-compacting concrete (SCC) made with 100% coconut water varies. The average compressive strength of SCC concrete with 100% coconut water is 41 kg/cm2 after 3 days, 88.67 kg/cm2 after 7 days, 242.67 kg/cm2 after 14 days, and 364 kg/cm2 after 21 and 28 days. 550.67 kg/cm2. The results of the normal compressive strength test showed growth; the average compressive strength was 284 kg/cm2 at 3 days, 511 kg/cm2 at 7 days, and 1386 kg/cm2 at 14 days. 21 days = 2226; 28 days equals 3098.67.